1999
DOI: 10.1038/sj.bjp.0702888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of A2A adenosine receptor stimulation and antagonism on synaptic depression induced by in vitro ischaemia in rat hippocampal slices

Abstract: 1 In the present study we investigated the role of A 2A adenosine receptors in hippocampal synaptic transmission under in vitro ischaemia-like conditions. 2 The e ects of adenosine, of the selective A 2A receptor agonist, CGS 21680 (2-[p-(2-carboxyethyl)-phenethylamino]-5'-N-ethylcarboxamidoadenosine), and of selective A 2A receptor antagonists, ZM 241385 (4-(2-[7-amino-2-(2-furyl)-{1,2,4}-triazolo{2,3-a}{1,3,5}triazin-5-ylamino]ethyl)phenol) and SCH 58261 (7-(2-phenylethyl)-5-amino-2-(2-furyl)-pyrazolo-[4,3-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 55 publications
6
45
0
Order By: Relevance
“…3 show that periods of 2-or 5-min OGD induced, respectively, a partial or complete reduction of synaptic potential amplitude that was always reversible upon reperfusion with normal oxygenated aCSF. These results are in agreement with our previous studies [13,27,28].…”
Section: Selective Block Of a 3 Adenosine Receptors By Mrs1523 Reducesupporting
confidence: 94%
See 4 more Smart Citations
“…3 show that periods of 2-or 5-min OGD induced, respectively, a partial or complete reduction of synaptic potential amplitude that was always reversible upon reperfusion with normal oxygenated aCSF. These results are in agreement with our previous studies [13,27,28].…”
Section: Selective Block Of a 3 Adenosine Receptors By Mrs1523 Reducesupporting
confidence: 94%
“…A decrease in fEPSP depression, brought about by A 3 agonists, hypothetically might be attributed to A 2A receptor stimulation. It was, in fact, previously demonstrated that selective stimulation of A 2A receptors by CGS 21680 decreases fEPSP depression induced by 2-min OGD and that the effect is antagonized by the selective A 2A antagonist ZM 241385 [28]. However, the concentration of Cl-IB-MECA used in the present study (10 nM) is highly selective for A 3 versus A 2A receptors [32], and the effect of Cl-IB-MECA is not antagonized by ZM 241385, indicating that Cl-IB-MECA-induced depression of fEPSP inhibition during 2-min OGD is not mediated by A 2A adenosine receptors.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations